Analisis Kebutuhan Bahan Ajar Educational Statistics Berbantuan Aplikasi SPSS bagi Mahasiswa Pendidikan Bahasa Inggris Universitas Pasir Pengaraian - Annajmi Annajmi; Batdal Niati (Peneliti.net, 2020)
The statistical education course is one of the compulsory courses taken by English language education students. Students must master and be proficient in statistics to support their needs in processing research results in their final project or thesis. However, based on student learning outcomes last semester, it is not known that the separation of the 24 students obtained a C value so this affects the ability of students to process research data, especially students who have research and observation methods. This problem is because students do not have study resources / statistical text books specifically for English research. This study aims to see the need for statistical teaching materials for special education in English education research. The method used is descriptive qualitative research with the research subjects of English education students at Pasir Pengaraian University who assess 30 students. Based on the results of the questionnaire data analysis and interviews conducted in the district, it is necessary to teach statistics for special education in the field of English with the help of the SPSS application. Teaching materials developed with simple case examples in the field of English research. The teaching materials developed will be tested at a later stage.